Development of Cutter Head Design in Cutter Suction Dredger with Thickness and Pitch Variation - Amiadji Amiadji; Achmad Baidowi; riyan prayogo (Institut Teknologi Sepuluh Nopember, 2019)
The need for dredgers for the shallow water in the sea with a very high level of siltation on the coast of Indonesia is a factor worth considering. For example, coastal areas in Ujung Pangkah sub-district, Gresik district, East Java province. The choice of the area is due to the many institutions and corporations that are back and forth utilizing these waterways. But the main obstacle to making a Cutter Suction Dredger (CSD) is almost all the equipment needed is imported, for example, the main equipment is the cutter head. Therefore looking at the needs, economics and technology factors, this paper will discuss the cutter head design. Available data is a request from the owner, 40KW power cutter head; 1000mm cutter diameter; 30rpm rotation. The force distribution given 5950 N is in accordance with the dredging condition which is to have a strong material tension to be estimated to work at a relatively Soft density of <100 Mpa and Medium around 100Mpa - 170Mpa. The expected results of this design are to obtain a proportional design before the production process and to function at a minimum according to specifications. The usefulness of this design really hopes to be followed up to the production stage and can be applied.